Finite element analysis on multi-toughening mechanism of microstructure of osteon. (May 2021) - Yin, Dagang; Chen, Bin; Lin, Shiyun
Abstract: The toughening mechanism of cortical bone is closely related to its hierarchical microstructure. Osteon is the most important microstructure of cortical bone. Therefore, it is very important to study the toughening mechanism of the microstructure of osteon. There are three main kinds of cracks in cortical bone: external crack of osteon, internal radial cracks of osteon and microporous damage cracks. Numerical models for these three kinds of cracks are established by XFEM and the progressive damage approach, respectively. The multi-toughening mechanisms of microstructure of osteon are found. The cement line on the outside of osteon is its first toughening mechanism, which can make the crack deflection and improve the fracture resistance of osteon. The resistance of cement line to fracture increases with the decrease of the strength and the increase of the thickness. The second toughening mechanism is elliptical osteocyte lacunae, which can attract the crack into the elliptical lacunae and cause stress redistribution to prevent the crack propagation. The annularly elliptical lacuna structure is an optimized arrangement and shape of microstructure, which is the third toughening mechanism of osteon. This microstructure can determine the location of the crack initiation and make the microcracks propagate along the annular direction rather than penetrating into the haversian cannal to protect the integrity of the osteon. The study of these toughening mechanisms provides new ideas for the research and design of synthetic composite structures.